2021
DOI: 10.1007/s11101-020-09733-1
|View full text |Cite
|
Sign up to set email alerts
|

Fruitful decade of fungal metabolites as anti-diabetic agents from 2010 to 2019: emphasis on α-glucosidase inhibitors

Abstract: In recent years the prevalence of diabetes has increased globally and by 2040 the number of diabetic people has been estimated to increase to 642 million. Various classes of drugs are available to treat Type ll diabetes. However, these drugs are associated with certain side effects. α-Glucosidase is an intriquing target enzyme to treat Type II diabetes, and α-glucosidase inhibitors are considered as first-line drugs for Type ll patients. Fungi, in general, produce natural products with some amazing chemical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 105 publications
0
9
0
Order By: Relevance
“…153 As their involvement in diabetes is understood, PTP1B and a-glucosidase are targets for the treatment of diabetes, and thus coumarins which inhibit the activity of these enzymes possess therapeutic potential. 154,155 In animal models, coumarins and their derivates exhibit protective effects against diabetes and associated renal damage. 156,157 Kang et al administered esculin, a coumarin derivative, to streptozotocin-induced diabetic mice and found that esculin combatted diabetesassociated symptoms including elevated blood glucose levels and increased hepatic glucose-6-phosphotase expression.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…153 As their involvement in diabetes is understood, PTP1B and a-glucosidase are targets for the treatment of diabetes, and thus coumarins which inhibit the activity of these enzymes possess therapeutic potential. 154,155 In animal models, coumarins and their derivates exhibit protective effects against diabetes and associated renal damage. 156,157 Kang et al administered esculin, a coumarin derivative, to streptozotocin-induced diabetic mice and found that esculin combatted diabetesassociated symptoms including elevated blood glucose levels and increased hepatic glucose-6-phosphotase expression.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…A series of isochromenone based polyketide molecules namely (+)‐diaportinol 1 and its analogs were isolated from ethyl acetate extract of cheese‐associated P. nalgiovense cultured on solid media by Larson group in 1999 [2] . Later, diaportinol 1 and its related secondary metabolites isolated from several other fungi sources [3] . Apart from food associated fungi, Gao and his team found racemic diaportinol in the cold adopted fungal strain Mucor sp .…”
Section: Figurementioning
confidence: 99%
“…Natural products might be a source of new herbicidal entities with potentially new modes of actions [ 5 ]. Fungi are considered as one of the richest sources of natural products among living organisms [ 6 ]. The phytotoxins produced by fungi are often suitable for the pathogenesis or infection of weeds [ 7 ].…”
Section: Introductionmentioning
confidence: 99%